Evaluation of selected physical properties of soil in the vineyard - Pavel Zemánek (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
There is registered approximately 18 000 ha of intensive vineyards in this time in Czech Republic. The intensive viticulture production is represented by high amount of working operations which are practised by using of mechanization. Frequency of passages by mechanization in interrow of descent is different by single variants of production processes. Their currently number varies about 20–25 per season. The soil compression is the highest in wheels tracked lines and middle of the interrow. If the compaction reaches over the critical limit, it can be this state escorted by weighty incidence (decrease of decree, increasing by power severity by soil cultivation and other). These contributions deal with analysis of soil compression in different areas in the region of the South Moravia. The used methods were undisturbed sample and penetration resistance with using of penetrometer.